Analyzing the time-frequency connectedness among oil, gold prices and BRICS geopolitical risks. (October 2021) - Li, Yingli; Huang, Jianbai; Gao, Wang; Zhang, Hongwei
Abstract: Based on the Barunik and Křehlik (2018) and Diebold Yilmaz (2012) methods, we examine the dynamic characteristics of the information spillover effect among gold, oil and BRICS geopolitical risks in different time and frequency domains. The results show that return and volatility spillovers are stronger in the short term than in the long term. The overall spillover is caused mainly by short-term spillover effects. In most cases, the oil market has a strong spillover relationship with the gold market. Furthermore, China's geopolitical risks have the greatest impact on gold, oil, and other countries' geopolitical risks. In addition, China's geopolitical risks are the only net contributor in the time domain, which indicates that China occupies an important position in the BRICS. Furthermore, geopolitical events can significantly increase the connectivity of the entire framework. Highlights: Relationship among oil, gold and BRICS geopolitical risks is analysed. Return and volatility spillovers over time and across frequencies are measured. We use the time-frequency domain spillover method of Diebold and Yilmaz (2012) and Barunik and Krehlik (2018). The return and volatility spillovers are stronger in the short term than in the long term. China's geopolitical risks have the greatest impact on gold, oil, and other countries' geopolitical risks.